Female Presence on Corporate Boards: A Multi-Country Study of Environmental Context - Terjesen, Siri; Singh, Val (Springer, 2008)
A growing body of ethics research investigates gender diversity and governance on corporate boards, at individual and firm levels, in single country studies. In this study, we explore the environmental context of female representation on corporate boards of directors, using data from forty-three countries. We suggest that women's representation on corporate boards may be shaped by the larger environment, including the social, political and economic structures of individual countries. We use logit regression to conduct our analysis. Our results indicate that countries with higher representation of women on boards are more likely to have women in senior management and more equal ratios of male to female pay. However, we find that countries with a longer tradition of women's political representation are less likely to have high levels of female board representation.
Keywords: Corporate Boards; Environmental Context; Female Directors; Gender; Multi-country; Pay Gap; Political Representation